A Study on the Contribution of Women in Shashi Despande’s Novels: Exploring the Empowerment of Women in Shashi Despande's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Shashi Deshpande, the contemporary Indo-English author has exhibited the strengthening of women by distinguishing themselves. She can be credited with having imaginatively sensationalized the urban working-class Indian life and centering the social, mental, and moral quandaries of females in India. In this study, we have discussed the Contribution of women in Shashi’s tales, recognition of women’s spirit, achievement of success – that long silence, recognition of women in roots and shadows, the role of women in the dark holds no terrors and roots and shadows which conclude that Women have been portrayed before as the instance of immaculateness and profound power and regarded as virtuous creatures from one viewpoint and on the other, saw as being frail animals always requiring the insurance of man as their ruler and ace.